Proposed Hybrid Takaful (islamic Insurance) Model For Mental Health Illnesses Among Low Income Earners In Malaysia - Khairil Faizal Khairi; Nur Hidayah Laili; Manh Dung Tran (The IJBMT, 2024)
Non-Indexed Publication